BIOETHICS OF EVERYDAY LIFE AND THE PRACTICE OF OBSTETRICS BASED ON ETHICAL AND MORAL PRINCIPLES: A CASE STUDY OF THE MIDWIFE OF AUSCHWITZ - de Souza, Ricardo Soares; de Souza, Heloisa Barros (Seven Editora, 2025)
Everyday bioethics, especially in the context of obstetrics, addresses the ethical and moral dilemmas that healthcare professionals face in the exercise of their duties. This area highlights the importance of fundamental ethical and moral principles, such as autonomy, beneficence, non-maleficence, and justice, which guide daily decisions in the care of pregnant women and newborns. In the exercise of their duties, they often encounter complex situations, such as managing risks during pregnancy and childbirth, making decisions about medical interventions, and providing emotional support to pregnant women. Patient autonomy is essential, as it involves respecting their choices and beliefs, even if they may diverge from medical recommendations. Finally, everyday bioethics in obstetrics is permeated by an unwavering commitment to the dignity and rights of women, challenging professionals to balance their vocation with ethical responsibilities in constantly changing environments. A prime example of an icon embodying the essence of bioethics in practice is Stanisława Leszczyńska, known as the Midwife of Auschwitz. She faced immense ethical and moral challenges while working as a midwife in inhumane conditions. As part of the Nazi concentration camp system, she was forced to deal with the reality of unwanted pregnancies and childbirths in an environment of horror. Her commitment to life and human dignity stood out amidst the genocide. Her main ethical challenges included the obligation to perform deliveries under extreme conditions, often without adequate resources. The women she attended were mostly prisoners, and many faced death after childbirth. She had to choose between saving the mother and the child, a choice that put her own safety at risk, since the Nazis showed no compassion for these women, and she became a symbol of humanism in the face of horror, leaving lessons about the importance of acting with integrity. Her testimony challenges us to reflect on how phenomena of pressure and oppression impact ethical issues in medicine and other professions. DOI: https://doi.org/10.56238/sevened2025.036-135